Studi Literatur implementasi fatwa DSN MUI No.73 tentang Musyarakah Mutanaqishah - Vauziah, Riva Adha; Muhammad, Fattah Muharrik; Rahmadin, Windi Laeli (Journal of Fiqh in Contemporary Financial Transactions, 2023)
The purpose of this study is to find out how the implementation of the musyarakah mutanaqishah contract on mortgage financing (KPR) in Indonesia. The research method used is a qualitative method using a literature review. The source of this research is in the form of journals obtained from Google Scholar with topics around the implementation of the Musyarakah Mutanaqishah contract on mortgage financing. This study uses descriptive statistical analysis based on 16 published articles related to the implementation of the musyarakah mutanaqishah contract published by Google Scholar. All sample journal publications have been published for eight years from 2015 to 2022. The results showed that there were 3 articles which stated that the MMQ contract had not been implemented according to the fatwa, there were 8 articles whose implementation was according to the fatwa and there were 5 articles which still had many deficiencies related to the implementation of the MMQ contract. . Furthermore, the most articles published were in 2018 (31%) and the fewest were in 2015 and 2022 (6%). Tujuan dari penelitian ini untuk mengetahui bagaimana implementasi akad musyarakah mutanaqishah pada pembiayaan kredit kepemilikan rumah (KPR) di Indonesia. Metode penelitian yang digunakan adalah metode kualitatif dengan menggunakan literatur review. Sumber penelitian ini berupa jurnal yang didapatkan dari google scholar dengan topik seputar implementasi akad Musyarakah Mutanaqishah pada pembiayaan KPR. Studi ini menggunakan analisis statistik deskriptif berdasarkan 16 artikel publikasi terkait dengan implementasi akad musyarakah mutanaqishah yang di publikasi google scholar. Seluruh publikasi jurnal sampel telah diterbitkan selama delapan tahun mulai 2015 hingga 2022. Hasil penelitian menunjukan bahwa ada 3 artikel yang menyebutkan akad MMQ belum diimplementasikan sesuai fatwa, ada 8 artikel yang pengimplementasiannya sesuai fatwa dan ada 5 artikel yang masih memiliki banyak kekurangan terkait pengimplentasian akad MMQ . Selanjutnya paling banyak artikel diterbitkan pada tahun 2018 (31%) dan paling sedikit yaitu tahun 2015 dan 2022 (6%).